2022
DOI: 10.1177/21674795211067471
|View full text |Cite
|
Sign up to set email alerts
|

Playoff Losses, Mayoral Politics, Image Repair, and Inoculation: Open Letter Sport Communication

Abstract: In May 2021, the Toronto Maple Leafs National Hockey League team lost a seventh and final playoff game—again. The day after their loss, Toronto Mayor John Tory took the unusual step of penning an open letter to Maple Leaf fans in response. His two-page letter was a unique mix of communication genres, including sport communication, political communication, and, with multiple references to COVID-19, health communication. It was also, as we argue here, a unique example of image repair rhetoric in general and spor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Research has also explored crisis communication efforts involving athletes accused of substance abuse (Allison et al, 2020; Hambrick et al, 2015) and athletes creating toxic work environments (Schmittel & Hull, 2015). IRT research has also explored how journalists employ IRT strategies on behalf of organizations (Sheffer et al, 2018) and how government officials utilize IRT following bad performances by local sport teams (Compton & Compton, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has also explored crisis communication efforts involving athletes accused of substance abuse (Allison et al, 2020; Hambrick et al, 2015) and athletes creating toxic work environments (Schmittel & Hull, 2015). IRT research has also explored how journalists employ IRT strategies on behalf of organizations (Sheffer et al, 2018) and how government officials utilize IRT following bad performances by local sport teams (Compton & Compton, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This research has demonstrated that journalists will engage in minimization and stonewalling tactics to repair the image of sport entities that exert significant power, and that sport media have a vested interest in covering (Sheffer et al, 2018). Additionally, research has revealed that government officials will engage in image repair following a team’s disappointing season by employing bolstering , attacking accusers , and corrective action (Compton & Compton, 2022). This research further contends that these tactics serve as an inoculation message, allowing fans to resist discouragement and maintain their support of the team.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In some conditions, scandals may threaten the existence of sports businesses or prompt them to make substantial organizational transformations (Storm & Wagner, 2015, p. 293). Schol-ars have examined sports scandals concerning doping (Duval, 2017;Engelberg et al, 2015;Galluzzi, 2000;Hermann, 2019;Laine, 2006), political intervention (Altukhov & Nauright, 2018;Harris et al, 2021;Leigh & McAllister, 2021), corruption (Andreff, 2019;Gardiner et al, 2017;Masters, 2015;Ncube, 2017;Philippou, 2021), governance structures Hanstad, 2008;Krieger, 2019;Mandel, 2016), media framing of scandal (Bie & Billings, 2015;Burch et al, 2015;Sanderson & Hambrick, 2012;Smith & Pegoraro, 2020;Stanley, 2021), awful defeats (Compton & Compton, 2014;Compton & Compton, 2022), and communication image repair (Allison et al, 2020;Glantz, 2010;Hambrick et al, 2015;Koa & Abu Hassan, 2022;Onwumechili & Bedeau, 2017;Smith & Keeven, 2019;Walsh & McAllister-Spooner, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%